Um em um milhão: a "excepcionalidade negra" e a negritude pelas visualidades cinematográficas nos Estados Unidos (1990-1999) - Silva, Eduardo Antonio da (2024)
This dissertation approach the issue of the exceptional negro in the visual culture of the United States, exploring the dynamics in which a black person's individual ascension is often related to competition and subalternization among their peers. The study highlights the persistence of inferiority towards white people, even when exists a black individual achieves prominence, thus maintaining white supremacy in a context of structural racism. The chapters explore the theoretical issues behind black exceptionality, a quantitative survey of film productions from the 1990s with black casts and an analysis of Spike Lee's works, providing a contrasting view of the black experience in the United States. Thus, in addition to the survey, mainstream productions were analyzed in which Samuel L. Jackson (Pulp Fiction, 1994 and Eve’s Bayou, 1997) and Whoopi Goldberg (Ghost, 1990; The Long Walk Home, 1990 and Sister Act, 1992) were in the cast, contrasting with the works of Spike Lee, contained in the so-called New Black Cinema, starting from the theory of Visual Studies to understand the moment of productions and the issue of the exceptional negro.